ANALISIS PERBEDAAN LIKUIDITAS SAHAM, ROI DAN EPS SEBELUM DAN SESUDAH STOCK SPLIT - Utami, Putri Dewi; Hermuningsih, Sri; Cahya, Agus Dwi (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study is to analyze the differences in Stock Liquidity, ROI, and EPS before and after the Stock Split in companies listed on the Indonesia Stock Exchange in the 2015-2019 period. The population in this study were all companies listed on the Indonesia Stock Exchange and conducted a Stock Split. The data used is secondary data, while the data source is obtained through www.idx.co.id. Of the 66 companies listed on the Indonesia Stock Exchange that carried out a stock split, only 10 companies met the criteria for the research sample that had been determined. The analysis technique is descriptive analysis, classical assumption test, hypothesis testing using paired sample t-test with the help of SPSS. The results showed that (1) there was a difference between stock liquidity before and after the stock split, this was indicated by the results of the 2 average difference test obtained because -t count -1.078 <2.011 -t table with a significance value of 0.03 <0 , 05 (2) there is a difference between Return On Investment before and after the stock split, this is indicated by the results of the average 2 difference test obtained because -t count -0.700 <2.011 -t table with a significance value of 0.001 <0.05 ( 3) there is no difference between EPS before and after the stock split, this is indicated by the results of the average 2 difference test obtained because - t count 1.204 <2.011 - t table with a significance value of 0.259> 0.05.Keywords: Stock Split, Stock Liquidity, Return On Investment (ROI), Earning Per Share (EPS